2006
DOI: 10.5465/amj.2006.21794663
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Organizational Identity Threats: Exploring the Role of Organizational Culture

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instruction, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
838
1
43

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,041 publications
(944 citation statements)
references
References 50 publications
25
838
1
43
Order By: Relevance
“…48 Necessarily, this involves the crafting of subjective heritage stories "as influential discursive resources for crafting a meaningful account of new claims and resolving possible divergences of interpretations about core and distinctive features." 49 A number of studies showed how organizations use heritage in a structured, collective interpretation to attach meaning to events and infuse value into organizational processes and outcomes. 50 One study of Cadbury candies indicated how, at three distinct points in its existence, the firm deliberately changed the emphasis of its heritage story to create competitive advantage by better meeting contemporary business needs.…”
Section: Heritage and Organizational Changementioning
confidence: 99%
“…48 Necessarily, this involves the crafting of subjective heritage stories "as influential discursive resources for crafting a meaningful account of new claims and resolving possible divergences of interpretations about core and distinctive features." 49 A number of studies showed how organizations use heritage in a structured, collective interpretation to attach meaning to events and infuse value into organizational processes and outcomes. 50 One study of Cadbury candies indicated how, at three distinct points in its existence, the firm deliberately changed the emphasis of its heritage story to create competitive advantage by better meeting contemporary business needs.…”
Section: Heritage and Organizational Changementioning
confidence: 99%
“…Most of the literature on organizational identity develops the idea that identity is a dynamic construct formed in interaction with organizational image (Dutton & Dukerich, 1991;Gioia, 1998) and organizational culture (Hatch & Schultz, 2002;Ravasi & Schultz, 2006). Organizational identity constitutes mental representations of how organizational members define themselves as a social group in terms of practices, norms, and values and understand themselves to be different from members of other organizations.…”
Section: Organizational Identitymentioning
confidence: 99%
“…Building on these conversations, a special issue of the Academy of Management Review in 2000 provided another basis for a comprehensive treatment of fundamental issues, with conceptual considerations of topics such as multiple identities ( Pratt and Foreman, 2000 ), self-categorization ( Hogg and Terry, 2000 ) and the dynamics possible in the interrelations between organizational identity and image ( Gioia et al ., 2000 ). These contributions not only built on empirical work carried out in previous years (eg Dutton and Dukerich, 1991 ;Gioia and Thomas, 1996 ), but also inspired and supported a renewed interest in empirical research (eg Foreman and Whetten, 2002 ;Dukerich et al ., 2002 ;Corley and Gioia, 2004 ;Corley, 2004 ;Ravasi and Schultz, 2006 ;Nag et al ., 2007 ), helping expand the boundaries of the fi eld and providing new insights on the concept itself.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, we can observe a progression of those debates to a more refi ned level (eg ' Where do identities originate from? ' (eg Glynn, 2000 ;Whetten and MacKey, 2002 )), and fi nally to the emergence of new ideas (eg the practical underpinning of organizational identities (eg Nag et al ., 2007 ) and the nature and impact of identity threats (eg Elsbach and Kramer, 1996 ;Ravasi and Schultz, 2006 )), as well as to connections with other areas of organizational science (eg identity and institutions ; Czarniawska, 1997 ;Hsu and Hannan, 2005 ;Whetten, 2006 ). 1 In using this special issue as a spark for new theoretical and empirical efforts aimed at furthering conceptual refi nement and integration, we decided to refl ect that maturation of the fi eld in the structure of the issue itself.…”
Section: Introductionmentioning
confidence: 99%